Concepts and Inspiration of Creating the Tale and Main Characters in Wat Koh “Thep Sam Ruedu” - Sanpinit, Pattaradhorn; Tansrisook, Sompornnuch (Journal of Cultural Approach, 2021)
This article studies Wat Koh tale entitled “SAM RUEDU” in Ratanakosin Era 108 version and 69 episodes of Thep Sam Ruedu and it analyzes concepts and inspiration for creating the tale and main characters. The result shows that the tale and drama contain main concepts based on Thai storytelling tradition and are consistent with the teachings of Buddhism which are karma, impermanence, and suffering from separation. The plot pattern is similar to a universal story with a melodramatic theme. This can be seen from the beginning. There was a deportation event that caused the separation between mother and son, Rāhu as a deportee, the adventures of the protagonist with helpers, the search for mates with an unnaturally sexual concept, and the suppression of the devil according to the concepts of “good always triumphs over evil.” The protagonists are three gods who are commanded to be reincarnated in the form of human beings and alternately appear in different seasons, namely, Phra Rāhu, Nang Jinda Mekhalā, and Phra Pheeroon. These god characters were inspired by myths and tales describing natural causes based on the incarnation and the concept of personification of nature that is associated with sky phenomena.